2020
DOI: 10.21037/apm-20-363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine on heart rate control and pre-operative outcome in patients with acute aortic dissection: a propensity-matched analysis

Abstract: Background: The total survival rate in patients with acute aortic dissection (AAD) has been greatly improved because of surgical technique advances. However, the pre-operative mortality rate remained high.In this study, we sought to evaluate the effects of dexmedetomidine (DEX) on heart rate control and preoperative outcome in AAD.Methods: Retrospectively enrolled 461 patients who were diagnosed with AAD during the first 7-day after admission and divided into two groups according to the use of intravenous DEX:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…At each time point during the arousal period, the HR of the observation group was lower than that of the control group. e difference may be caused by the inhibition of sympathetic nerve excitement by dexmedetomidine [18]. However, from the point of view of adverse reactions, this inhibitory effect was not serious, and the incidence of adverse reactions of dexmedetomidine during intraoperative wake-up was significantly lower than that of the control group.…”
Section: Discussionmentioning
confidence: 89%
“…At each time point during the arousal period, the HR of the observation group was lower than that of the control group. e difference may be caused by the inhibition of sympathetic nerve excitement by dexmedetomidine [18]. However, from the point of view of adverse reactions, this inhibitory effect was not serious, and the incidence of adverse reactions of dexmedetomidine during intraoperative wake-up was significantly lower than that of the control group.…”
Section: Discussionmentioning
confidence: 89%
“…showed that it can inhibit in ammatory response, improve myocardial ischemia-reperfusion injury, and reduce the cardiovascular response during surgery, thereby stabilizing hemodynamics [20]. Studies have shown that preoperative pretreatment and intraoperative perfusion of dexmedetomidine can reduce heart rate and blood pressure to a certain extent, reduce myocardial oxygen consumption, and contribute to the recovery of damaged myocardium and stable heart rate [21]. Neostigmine, as a cholinesterase inhibitor and as a muscle relaxant antagonist, is often used postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed that DEX administration in patients with Stanford type A AD significantly reduced the use of anti-hypertensive drugs and the required morphine dose. In addition to its sedative effect, DEX is a highly selective α2 adrenergic agonist which could effectively inhibit the production of stress-related catecholamine [Chen 2020], and also exert a synergistic effect with opioids, thus reducing the dose of sedatives and attenuating the impact of morphine on respiration [Xu 2016]. Although this phenomenon was not observed in Stanford type B AD patients, we speculate that it may be because the incidence of pain and the dosage of antihypertensive drugs in Stanford type B AD patients were lower than in type A AD patients.…”
Section: E492mentioning
confidence: 99%